Towards Adab-Based Hybrid Authority: A Dialectic between Classical Islamic Ethics and Society Algorithms 5.0 - Mahfud, Mahfud; Maarif, Mohammad Syamsul (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2026)
The educational transformation of Society 5.0 has increasingly positioned machines as autonomous pedagogical agents, raising critical questions about the relationship between adab and algorithms in Islamic education. This study aimed to analyze the dialectic between these two constructs, address the literature gap concerning the ethical depletion risks associated with artificial intelligence, and examine the threat such developments pose to the sacredness of knowledge transmission in the Islamic tradition. More specifically, the study sought to deconstruct claims that machines can assume the role of the teacher while reaffirming the primacy of the human educator. Employing a descriptive-philosophical literature design, the study used purposive selection of authoritative works by Ashʿarī, al-Zarnūjī, al-Ghazālī, Ibn Khaldūn, and al-Ḥaddād, which were dialectically synthesized with 21 articles from reputable international journals published between 2021 and 2026 and verified through Scimago Journal Rank. The findings indicate that, ontologically, machines function only as pedagogical tools because they lack spirit and nafs, and therefore cannot form learners who require spiritual exemplarity (uswah). The study’s main theoretical contribution is the formulation of the Adab-Based Hybrid Authority (ABHA) model as a framework for integrating technology on the basis of moral-spiritual authority. The study concludes that within the digital educational ecosystem, machines should be repositioned as supporting instruments, while humans must remain the muʿaddib. This conclusion reinforces a human-centric paradigm in the philosophy of Islamic education and highlights the practical need to redefine the teacher’s role as a moral filter. The study therefore recommends redesigning teacher education curricula on the basis of digital ethics and identifies future research opportunities concerning the long-term psycho-spiritual impact of AI interaction in Islamic educational institutions.